Description and outcomes of obstetric patients admitted to the high care are (HCA) at Charlotte Maxeke Johannesburg academic hospital - Zulu, Siyanda Mlungisi Joshua (My University, 2019)
Background Critical obstetric care in the developed world has been shown to be a useful tool in reducing maternal morbidity and mortality. Despite this there has been few studies in the developing world and in particular South Africa which looked into the incidence, risk factors and characteristics of patients requiring such a specialised service. This information could assist in improving patient care and clinical outcomes. Hence the aim of the study was to describe the characteristics and outcomes of patients admitted to the obstetrics high care area (HCA) at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH). Methods This was a retrospective record review of patients admitted to the obstetrics HCA at CMJAH during the period 1 January to 30 June 2016. Labour ward, theatre, HCA and intensive care unit (ICU) registers were used to identify patients included in the study. Patient records were retrieved from the hospital’s records area. A standardised data collection tool was used to extract the following information from patients’ files: demographics, indications for admission to HCA, management and outcomes. Descriptive statistics were used to analyse the data. Results A total of 114 patients were admitted to the HCA during the study period. The most common obstetric reason for HCA admissions was pre-eclampsia (58.8%, n=67/114) and its associated complications which included HELLP syndrome (12.3%, n=14/114) and eclampsia (7.0%, n=8/114), followed by obstetric haemorrhage (28.1%, n=32/114). Cardiac diseases (12.3%, n=14/114), followed by pneumonia (5.3%, n=6/114) were the most common non-obstetrics reasons for HCA admissions. The majority of these patients had a short HCA stay, 1 to 2 days. Most of the patients were discharged alive (86.8%, n=99/114) and 11 (9.6%) were transferred to ICU. Out of the 11 patients who went to ICU, seven were transferred back to HCA well and four were maternal deaths. Two of the maternal deaths were due to complications of eclampsia, one had jaundice with hepatosplenomegaly of unknown cause, and the fourth patient had metastatic breast cancer. Conclusion Pre-eclampsia, and its complications which included HELLP syndrome and eclampsia, obstetric haemorrhage, cardiac diseases and pneumonia were the most common reasons why obstetric patients required HCA and ICU admission. Most of the obstetric patients with complications were managed successfully in HCA and only a small percentage required ICU admission. From the study, a conclusion can be made that most of the common obstetric complications that the study cohort presented with could be successfully managed in a high care setting, hence reducing the need for ICU which is more expensive.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in Obstetrics and Gynaecology MMed (O&G) Johannesburg, October 2019